Step
*
1
2
1
1
of Lemma
general-cantor-to-int-uniform-continuity
1. n : ℕ
2. B : ℕ ⟶ ℕ+
3. F : (k:ℕ ⟶ ℕB[k]) ⟶ ℤ
4. ⇃(∃n:ℕ. ∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕn ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ)))
5. ⇃(∃n:ℕ
      ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕn ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ)))
      ∧ (∀j:ℕ. ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕj ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))) 
⇒ (n ≤ j)))))
6. a2 : ∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕn ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))
7. a3 : ∀j:ℕ. ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕj ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))) 
⇒ (n ≤ j))
8. b2 : ∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕn ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))
9. b3 : ∀j:ℕ. ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕj ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))) 
⇒ (n ≤ j))
⊢ <a2, a3>
= <b2, b3>
∈ ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕn ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ)))
  ∧ (∀j:ℕ. ((∀f,g:i:ℕ ⟶ ℕB[i].  ((f = g ∈ (i:ℕj ⟶ ℕB[i])) 
⇒ ((F f) = (F g) ∈ ℤ))) 
⇒ (n ≤ j))))
BY
{ (Unfold `and` 0
   THEN EqCD
   THEN All (Unfolds ``all implies``)
   THEN Repeat ((FunExt THENW Auto))
   THEN GenConclAtAddr [2]
   THEN GenConclAtAddr [3]) }
1
1. n : ℕ
2. B : ℕ ⟶ ℕ+
3. F : (k:ℕ ⟶ ℕB[k]) ⟶ ℤ
4. ⇃(∃n:ℕ. (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)))
5. ⇃(∃n:ℕ
      ((f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ))
      ∧ (j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j))))
6. a2 : f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)
7. a3 : j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j)
8. b2 : f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)
9. b3 : j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j)
10. f : i:ℕ ⟶ ℕB[i]
11. g : i:ℕ ⟶ ℕB[i]
12. x : f = g ∈ (i:ℕn ⟶ ℕB[i])
13. v : (F f) = (F g) ∈ ℤ
14. (a2 f g x) = v ∈ ((F f) = (F g) ∈ ℤ)
15. v1 : (F f) = (F g) ∈ ℤ
16. (b2 f g x) = v1 ∈ ((F f) = (F g) ∈ ℤ)
⊢ v = v1 ∈ ((F f) = (F g) ∈ ℤ)
2
1. n : ℕ
2. B : ℕ ⟶ ℕ+
3. F : (k:ℕ ⟶ ℕB[k]) ⟶ ℤ
4. ⇃(∃n:ℕ. (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)))
5. ⇃(∃n:ℕ
      ((f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ))
      ∧ (j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j))))
6. a2 : f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)
7. a3 : j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j)
8. b2 : f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕn ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)
9. b3 : j:ℕ ⟶ (f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)) ⟶ (n ≤ j)
10. j : ℕ
11. x : f:(i:ℕ ⟶ ℕB[i]) ⟶ g:(i:ℕ ⟶ ℕB[i]) ⟶ (f = g ∈ (i:ℕj ⟶ ℕB[i])) ⟶ ((F f) = (F g) ∈ ℤ)
12. v : n ≤ j
13. (a3 j x) = v ∈ (n ≤ j)
14. v1 : n ≤ j
15. (b3 j x) = v1 ∈ (n ≤ j)
⊢ v = v1 ∈ (n ≤ j)
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  B  :  \mBbbN{}  {}\mrightarrow{}  \mBbbN{}\msupplus{}
3.  F  :  (k:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[k])  {}\mrightarrow{}  \mBbbZ{}
4.  \00D9(\mexists{}n:\mBbbN{}.  \mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g))))
5.  \00D9(\mexists{}n:\mBbbN{}
            ((\mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g))))
            \mwedge{}  (\mforall{}j:\mBbbN{}.  ((\mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g))))  {}\mRightarrow{}  (n  \mleq{}  j)))))
6.  a2  :  \mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g)))
7.  a3  :  \mforall{}j:\mBbbN{}.  ((\mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g))))  {}\mRightarrow{}  (n  \mleq{}  j))
8.  b2  :  \mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g)))
9.  b3  :  \mforall{}j:\mBbbN{}.  ((\mforall{}f,g:i:\mBbbN{}  {}\mrightarrow{}  \mBbbN{}B[i].    ((f  =  g)  {}\mRightarrow{}  ((F  f)  =  (F  g))))  {}\mRightarrow{}  (n  \mleq{}  j))
\mvdash{}  <a2,  a3>  =  <b2,  b3>
By
Latex:
(Unfold  `and`  0
  THEN  EqCD
  THEN  All  (Unfolds  ``all  implies``)
  THEN  Repeat  ((FunExt  THENW  Auto))
  THEN  GenConclAtAddr  [2]
  THEN  GenConclAtAddr  [3])
Home
Index